Study on the hot deformation behavior of SAE8620RH gear steel. Issue 1 (1st December 2022) - Chen, Songjun; Li, Liejun; Li, Jiao; Xie, Dongsheng; Zhu, Chenghui
Abstract: The rapid development of new energy vehicles has put forward higher requirements for the performance and precision of high-end gears. Reasonable thermal deformation parameters play a major role in controlling mechanical properties of gear steel. The stress-strain curves of the SAE8620RH gear steel were obtained by a single-pass compression test combined with the Gleeble-3800 simulator, and the effect of thermal deformation parameters on dynamic softening behaviour was analyzed. Results showed that with deformation temperatures increasing, dynamic softening mechanism changed from dynamic recovery to dynamic recrystallization. Increasing the strain rate inhibited dynamic recrystallization. However, under the condition that full dynamic recrystallization could have occurred; Higher strain rates can produce finer recrystallized grains. In addition, dynamic recrystallization grains were unevenly distributed and appeared to have abnormal grain growth at low strain rate and high temperatures.